Cinnamic Acid Toxicity on the Structural Resistance and Photosynthetic Physiology of Faba Bean Promoted the Occurrence of Fusarium Wilt of Faba Bean, Which Was Alleviated Through Wheat and Faba Bean Intercropping - Yang, Wenhao; Guo, Yuting; Li, Yu; Zheng, Yiran; Dong, Kun; Dong, Yan (Frontiers in Plant Science, 2022)
Background: The pattern of intercropping wheat and faba bean is an effective means to alleviate continuous cropping obstacles. Aim: To study the mechanism by which cinnamic acid promotes faba bean wilt and the mechanism by which intercropping alleviates this effect. Methods: Hydroponics was used to study the effects of inoculation with or without Fusarium oxysporum f. sp. fabae (FOF) and added different concentrations of cinnamic acid under inoculation FOF on faba bean seedling growth, Fusarium wilt, stem cell wall degrading enzyme activity, lignin content, tissue structure of the stem and leaf photosynthesis in monocropping and intercropping systems. Results: Treatment with FOF significantly reduced the biomass and leaf photosynthesis of faba bean compared with the control. Microscopic observation showed that the xylem vessels of the stem were slightly thickened. Compared with FOF alone, the combination of FOF and cinnamic acid stress significantly increased the activity of cell wall degrading enzymes (CWDEs) produced by FOF in the stem and content of lignin in the stem. Microstructural observation showed that cell wall thickening of the xylem conduit, stratification, formation of a cavity and even the dispersion of tissue cell structure occurred in the stem tissue of faba bean. Furthermore, the biomass and leaf photosynthesis of faba bean decreased significantly, and the occurrence of faba bean wilt was increased. Compared with the faba bean monocropping treatment, the wheat and faba bean intercropping treatment significantly reduced the activity of CWDEs of FOF produced in faba bean stems, and increased the lignin content. In addition, observation of the microstructure indicated that the tissue structural cell wall thickened after the stem had decreased, the amount of colloidal substances and their containment decreased, causing a further decrease in tissue deformation, smaller intercellular spaces, less divided layer cell damage, an increase in the aboveground biomass and leaf photosynthesis of faba bean and a decrease in the occurrence of faba bean wilt. Conclusion: Cinnamic acid decreased the resistance of tissue structure cell to promote the occurrence of wilt. Wheat and faba bean intercropping improved the resistance of tissue structure cell to reduce the occurrence of wilt.